PEDAGOGICAL CONDITIONS FOR DEVELOPING THE CREATIVE POTENTIAL OF FUTURE SHIP’S MECHANICS (Innovative professional education, 2024)
The subsection considers the pedagogical conditions for the development of the creative potential of future ship mechanics in the process of professional training. The essence of pedagogical conditions in the educational process of a maritime professional higher education institution and their influence on the development of future ship mechanics’ creative potential is revealed
Keywords: creative potential; future ship mechanics; factors; pedagogical conditions; vocational higher education